The importance of biochemical indicators in determining male infertility - Nazarova, Gunay Elshan (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Recently, infertility has become a global problem and the frequency of the “male” factor in family infertility has reached 40-50%. The aim of the research is to investigate the role of some biochemical indicators (endocrine factors and fructose) in determining male infertility. Material and methods. In the study, the spermogram of 101 men aged 20–46 with idiopathic male infertility, the concentration of follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin and testosterone hormones in their blood, and the concentration of fructose in their sperm samples were analyzed, and their correlations were determined. Results. The concentration of FSH in the blood serum of men with asthenozoospermia and oligozoospermia increased statistically significantly by 57.7% and 2.4 times, respectively, compared to the control. More serious endocrinological disorders were recorded in men with azoospermia. In men with non-obstructive azoospermia, the concentration of FSH is 8.8 times, that of LH is 2.9 times; while prolactin increased by 89.0% compared to the control, testosterone concentration decreased by 22.9%. The fructose concentration in the oligozoospermia group compared to the control group increased by 60.8% (pH1<0.001), and in the non-obstructive azoospermia group by 2.0 times (pH1=0.001). A positive correlation between FSH and LH and a negative correlation between fructose concentration and forward motility of spermatozoa were determined in both asthenospermic and oligozoospermic patients (ρ=0.544; p=0.002). In case of non-obstructive azoospermia, FSH and prolactin, in azoospermia, LH and testosterone were directly proportional. Conclusion. During male infertility, there is a serious relationship between sperm indicators and endocrine disorders. An increase in the concentration of fructose is the main indicator of a decrease in the number and motility of spermatozoa. A high concentration of FSH and LH in men with azoospermia can be considered one of the important indicators in the diagnosis of non-obstructive azoospermia.
Permission to conduct the study was obtained from the Ethics Committee. The study plan was implemented in accordance with the Helsinki Final Act and the protocol was approved by the Ethics Committee Azerbaijan Medical University ICE Committee on Medical Sciences (No8. 28.06.2020).
Keywords: FSH; LH; male infertility; prolactin and fructose